الرضا الوظيفي وظروف العمل في قطاع البنوك الأردنية - الزعبي، محمد عمر; الملكاوي، أحمد فواز (جامعة عدن - كلية الاقتصاد, 2013)
هدفت هذه الدراسة إلى إلقاء الضوء على اتجاهات الموظفين البنوك الأردنية ومدى مساهمة توافر ظروف العمل تحقيق الرضا الوظيفي للموظفين، ومحاولة ايجاد علاقة بين زيادة الإنتاجية ومدى توافر ظروف العمل المناسبة.\ اعتمدت الدراسة الحالية على عينة عشوائية لعدد من الموظفين العاملين في البنوك الأردنية بلغ قوامها(60) شخصا، وتم اختيار الفئات العمرية(21-64) عاماً.\ توصلت الدراسة الحالية إلى عدد من النتائج البحثية، كان أهمها:\ 1-\ يعمل الموظفين بشكل أفضل كلما كانت ظروف العمل مناسبة.\ 2-\ يفضل الموظفين العمل في ظروف ملائمة وتمتاز بالمرونة من حيث ساعات العمل وظروف الموظفين مما يحسن من كفاءتهم وإنتاجيتهم ويحقق رضاهم الوظيفي.\ 3-\ على المدراء ومالكي البنوك إعطاء جميع الموظفين نفس الأولوية في تحقيق ظروف العمل المناسبة والمرنة للجميع.\ 4-\ الترقيات والمكافئات غير العادلة قد تؤدي إلى عدم رضا الموظفين ويزيد من الدوران الوظيفي.\ 5-\ تحسين ظروف عمل الموظف يعزز معنويات ويساعد المؤسسة في البقاء في السوق ويجذب الكفاءات ويقلص من الدروان الوظيفي بين العاملين.\ 6- تقييم الأداء المستمر يزيد من أداء الموظفين ويحقق لهم الرضاء الوظيفي بشكل افضل.\ وقد توصلت الدراسة إلى مجموعة من التوصيات كان أسها:\ 1- من الضروري تحقيق المرونة في العمل مما يجعل الموظفين أكثر رضاء ويحسن من إنتاجيتهم وكفاءتهم.\ 2- من الهم توفير جو ملائم من قبل المدراء ومالكي البنوك مثل (مكان عمل أمن، مكان عمل صحي)\ 3- من الهم إعطاء الموظفين حوافز مادية ومعنوية لزيادة إنتاجيتهم وولائهم للمؤسسة وزيادة رضاهم الوظيفي. This study has been set to explore attitudes to work life balance and flexible working practices, amongst employees who currently work full time in Jordanian bank sectors, and find out the relation between productivity and work life balance. \ This study presents finding from the job satisfaction and work life balance employee survey, a survey study in April 2010, respondents were taken of working age (21 to 64 for men and women) working in Jordan as employees in banking sector ,employing two or more employees at the same time of the survey. \ In order to reach this specific target we prefer to use the Questionnaire way. \ The sampling strategy used for this survey needed to be representative of people who are currently employed in banking sector. \ The survey will be distributed to the concerned employees in the mentioned banks. \ However, the outcome results will help us to better evaluate our survey. \ And the sample were have been drawn from 60 employees randomly from 200 employees taken from the scholastic community. \ This means that the sample represents 30% of the community. \ The most important research findings of the . study include the followings: \ 1.\ Most of the employees work better when they can balance their work and other aspects of their lives especially when having feedback. \ 2.\ Employees prefer to work in organizations where they have flexible management in which employees are allowed to take breaks and time off in emergency situations during working hours so these practices improve the workers' effectiveness and efficiencies to become more satisfied with their job. \ 3.\ Employers should give all employees the same priority when considering requests to work flexibly. \ 4.\ Unfair promotion practices could make the employees dissatisfied with their life outside work. \ 5.\ Improving employee work-life balance helps bolster morale and enables firms to retain and attract better quality workers. \ 6.\ Continuous performance tracking and communication of performance results by the superiors at work gives the employees better satisfaction with life outside work. \ The study made a number of recommendations. The most important \ were: \ 1.\ its important to apply more flexibility at work to make employees more satisfied so as to improve productivity. \ 2.\ Employers should give their employees the convenience atmosphere (healthy and secure place) to work better. \ 3.\ Giving the employees incentives such as (promotions, bonuses, time off .... etc) to increase their productivity, loyalty and their job satisfaction.
بحث منشور باللغة الإنجليزية
Keywords: الولاء و البراء -- الرضا الوظيفي -- البنوك -- الأردن -- الموظفون -- الحوافز -- الإنتاجية -- مستخلصات البحوث